2015
DOI: 10.1186/s12913-015-0983-0
|View full text |Cite
|
Sign up to set email alerts
|

Empowering patients through eHealth: a case report of a pan-European project

Abstract: BackgroundThis paper crystallises the experience developed by the pan-European PALANTE Consortium in dealing with the generation of relevant evidence from heterogeneous eHealth services for patient empowerment in nine European Regions. The European Commission (EC) recently funded a number of pan-European eHealth projects aimed at empowering European patients/citizens thus transforming the traditional patient/citizen role in the management of their health (e.g., PALANTE, SUSTAIN, CARRE, HeartCycle, Empower). Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
0
28
0
4
Order By: Relevance
“…A new organization of care seems needed for addressing appropriately the challenge of MM, which requires proactive integrated initiatives, especially for older people [12]. In this respect, eHealth solutions-i.e., the application of innovative Information and Communication Technologies (ICTs) in the healthcare sector [13]-have the potential to provide new tailored integrated care services to patients with MM, also supporting patient centeredness, self-management, and multidisciplinary care [14,15]. In fact, eHealth tools can offer to patients with MM relevant improvements for accessing personalized healthcare services and can enable new opportunities for treatment, rehabilitation, and maintaining healthy lifestyles and well-being [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new organization of care seems needed for addressing appropriately the challenge of MM, which requires proactive integrated initiatives, especially for older people [12]. In this respect, eHealth solutions-i.e., the application of innovative Information and Communication Technologies (ICTs) in the healthcare sector [13]-have the potential to provide new tailored integrated care services to patients with MM, also supporting patient centeredness, self-management, and multidisciplinary care [14,15]. In fact, eHealth tools can offer to patients with MM relevant improvements for accessing personalized healthcare services and can enable new opportunities for treatment, rehabilitation, and maintaining healthy lifestyles and well-being [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some evidences [4] in particular indicated that inclusion of eHealth tools in integrated approaches has the potential to increase safety and quality of care for patients, by providing continuity across health and social services. However, there are various potential barriers hampering the implementation of eHealth technologies targeting people with MM [36,40], such as lack of legislative regimes, lack of dedicated/adequate funding, limited privacy/ethics policies, and low adequate ICT infrastructures; also, cultural resistance to adopt technology both by patients and professionals [14], and lack of interoperability between eHealth applications [41] represent further barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients can overcome barriers for accessing healthcare services and also benefit from better monitoring and continuity of care, improved selfcare/management and independent living at home (especially for the older people). Yet various regulatory, technical and economic barriers exist that may limit the adoption of eHealth technologies [17,20,23], in addition to lacking/limited digital skills or cultural resistance of potential users, especially older patients [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the UK, it significantly increased in popularity during the 1990s and early 2000s. It was (also) a reaction to the sustainability crisis faced by the NHS (Anderson and Gillam 2001;Lettieri et al 2015). This prompted the Government to pivot towards a new proactive paradigm of healthcare provision (Moerenhout et al 2018), focused on delivering 'P4' (personalised, preventative, predictive and participatory) medicine (van Roessel et al 2017).…”
Section: The Roots Of the Empowerment Narrativementioning
confidence: 99%
“…There is, therefore, a need to start with understanding what empowerment actually means and build from there to a more complex critical analysis of the way in which it is operationalised in digital health strategy. This is difficult because the term itself is poorly defined (Lettieri et al 2015;Bravo et al 2015;Tengland 2007Tengland , 2008 and-despite the fact that the vociferous use of 'empowerment' by politicians, policymakers, clinicians, and technology providers may seem to indicate otherwise-it is used both loosely and inconsistently (Roberts 1999) by all these groups. A scoping review completed by Bravo et al (2015) found that even the most commonly used definition was still only used in 11% of the literature they reviewed.…”
Section: The Roots Of the Empowerment Narrativementioning
confidence: 99%